Why we need a Citizen's Basic Income : the desirability, feasibility and implementation of an unconditional income / Malcolm Torry. - Torry, Malcolm, 1955- (Policy Press, 2018)
This fully updated and revised edition includes new material to move the debate around Basic Income on from one of desirability to that of feasibility and implementation.